2018
DOI: 10.1053/j.gastro.2017.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Genotype Hepatitis E Virus Replication in Stem Cell–Derived Hepatocellular Systems

Abstract: Cell culture adaptations alter the replicative capacities of HEV. HLCs offer an improved, physiologically relevant, and genetically tractable system for studying the replication of primary HEV isolates. HLCs could provide a model to aid development of HEV drugs and a system to guide personalized regimens, especially for patients with chronic hepatitis E who have developed resistance to ribavirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 46 publications
7
62
7
1
Order By: Relevance
“…Therapeutic alternatives have been evaluated in vitro and in vivo. Sofosbuvir (SOF), a drug targeting the HCV NS5B polymerase, has shown to have an inhibitory effect on HEV replication [60]. Furthermore, the combination of SOF and RBV have demonstrated a cumulative effect for inhibiting HEV viral replication, suggesting a potential alternative approach.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic alternatives have been evaluated in vitro and in vivo. Sofosbuvir (SOF), a drug targeting the HCV NS5B polymerase, has shown to have an inhibitory effect on HEV replication [60]. Furthermore, the combination of SOF and RBV have demonstrated a cumulative effect for inhibiting HEV viral replication, suggesting a potential alternative approach.…”
Section: Discussionmentioning
confidence: 99%
“…2). HLCs offer an improved, physiologically relevant traceable system for studying the replication and antiviral response of primary HEV isolates (Wu et al, 2018). Previously, silvestrol has been mainly characterized in antitumor models such as chronic lymphocytic leukemia, acute lymphocytic leukemia, mantle cell lymphoma and also hepatocellular carcinoma (Cencic et al, 2009;Lucas et al, 2009;Alinari et al, 2012;Kogure et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Next, we evaluated the antiviral effect of silvestrol in HEV infection experiments using cell culture-derived infectious HEV (HEV CC ) based on the p6 isolate (Dao Thi et al, 2016) in HepG2/C3A cells and patientderived HEV of gts 1-4 in pluripotent stem cell-derived hepatocyte-like cells (HLCs) (Wu et al, 2018). At first, we evaluated the antiviral activity of silvestrol with the HEVp6 replicon in the HepG2/C3A cell line and observed a shift of the dose-response curves in comparison to Huh7.5 (suppl.…”
Section: Inhibition Of Cell Culture-and Patient-derived Hev Infectionmentioning
confidence: 99%
“…Wu et al reported that human iPS-Heps are permissive for non-cell culture-adopted HEV in contrast to hepatoma cells. HEV replication induces an antiviral innate immune response in iPS-Heps [49]. These reports indicate that human iPS-Heps can be used as an experimental model to develop antiviral agents against HCV and HEV.…”
Section: Disease Models Of Hepatitis C Virus (Hcv) and Hepatitis E Vimentioning
confidence: 90%